Polypharmacy and mortality association by chronic kidney disease status: The REasons for Geographic And Racial Differences in Stroke Study. Issue 4 (2nd August 2021) - Cashion, Winn; McClellan, William; Judd, Suzanne; Goyal, Abhinav; Kleinbaum, David; Goodman, Michael; Prince, Valerie; Muntner, Paul; Howard, George
Abstract: Many Americans take multiple medications simultaneously (polypharmacy). Polypharmacy's effects on mortality are uncertain. We endeavored to assess the association between polypharmacy and mortality in a large U.S. cohort and examine potential effect modification by chronic kidney disease (CKD) status. The RE asons for G eographic A nd R acial D ifferences in S troke cohort data ( n  = 29 627, comprised of U.S. black and white adults) were used. During a baseline home visit, pill bottle inspections ascertained medications used in the previous 2 weeks. Polypharmacy status (major [≥8 ingredients], minor [6–7 ingredients], and none [0–5 ingredients]) was determined by counting the total number of generic ingredients. Cox models (time‐on‐study and age‐time‐scale methods) assessed the association between polypharmacy and mortality. Alternative models examined confounding by indication and possible effect modification by CKD. Over 4.9 years median follow‐up, 2538 deaths were observed. Major polypharmacy was associated with increased mortality in all models, with hazard ratios and 95% confidence intervals ranging from 1.22 (1.07–1.40) to 2.35 (2.15–2.56), with weaker associations in more adjusted models. Minor polypharmacy was associated with mortality in some, but not all, models. The polypharmacy–mortality association did not differ by CKD status. While residual confounding by indication cannot be excluded, in this large American cohort, major polypharmacy was consistently associated with mortality. Abstract : Polypharmacy was associated with all‐cause mortality in a dose‐response fashion in the REGARDS cohort. Although having CKD is an independent mortality risk factor, there was no evidence of a greater polypharmacy mortality effect in those with CKD than those without CKD.